The impact of local government debt governance on carbon emissions: evidence from Chinese cities - Zhang, Yan; Kong, Jun (Frontiers in Environmental Science, 2025)
IntroductionIntegrating debt risk mitigation and carbon reduction is essential for superior economic development.MethodsThe study has selected panel data from 274 Chinese cities from 2009 to 2020 as the research sample. The 2015 Local Government Debt Governance (LGDG) is employed as an exogenous policy shock to examine the impact of LGDG on carbon emissions through the intensity difference-in-difference method (IDID).ResultsResearch findings indicate that after implementing LGDG policies, each city in the treatment group achieved an average reduction in carbon emissions of 1.1851 tonnes per capita compared to the control group. The conclusions remain robust after applying various tests, including stepwise regression, parallel trend tests, placebo tests, substitution of core variables, controlling for contemporaneous policies, changing the estimation method and using instrumental variables. Mechanism analyses show that LGDG achieves carbon reduction by reducing ’land resource mismatches’ and ’economic infrastructure investments.’ Heterogeneity analysis indicates that when marketization is relatively high, economic development pressures are low, environmental regulations are stringent, and geographical location is in the central and western regions, LGDG has a more pronounced effect on reducing carbon emissions.DiscussionThe research findings offer feasible pathways for coordinated governance of implicit debt risks and carbon emissions, providing practical insights for achieving carbon peaking and neutrality goals.